2006
DOI: 10.1111/j.0021-9029.2006.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Death Qualification in Venirepersons' Attitudes Toward the Insanity Defense1

Abstract: Three hundred venirepersons from the 12 th Judicial Circuit in Florida completed a booklet of stimulus materials that contained the following: one question that specified participants' level of support for the death penalty; one Witt death-qualification question; a case scenario that included a summary of the guilt and penalty phases of a capital case; verdict and sentencing preferences; a 16-item measure that required participants to rate their receptiveness to the insanity defense on a 6-point Likert scale; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 26 publications
4
26
0
1
Order By: Relevance
“…The present findings replicate an earlier body of research that concluded that the process of death qualification results in the seating of differentially partial jurors (Luginbuhl, 1992;Diamond, 1993;Wiener, Prichard, & Weston, 1995;Lynch & Haney, 2000;Butler & Moran, 2002;Butler & Wasserman, 2006). In addition, the current study extends previous findings by demonstrating that simply selecting a jury for a capital case systematically excludes certain personality types while systematically including others.…”
Section: Discussionsupporting
confidence: 88%
“…The present findings replicate an earlier body of research that concluded that the process of death qualification results in the seating of differentially partial jurors (Luginbuhl, 1992;Diamond, 1993;Wiener, Prichard, & Weston, 1995;Lynch & Haney, 2000;Butler & Moran, 2002;Butler & Wasserman, 2006). In addition, the current study extends previous findings by demonstrating that simply selecting a jury for a capital case systematically excludes certain personality types while systematically including others.…”
Section: Discussionsupporting
confidence: 88%
“…The present findings replicate an earlier body of research that concluded that the process of death qualification results in the seating of differentially partial jurors (Butler & Moran, 2002;Butler & Wasserman, 2006;Diamond, 1993;Luginbuhl, 1992;Lynch & Haney, 2000;Wiener, Prichard, & Weston, 1995). In addition, the current study extends previous findings by demonstrating that simply selecting a jury for a capital case systematically excludes people who have the ability and/or motivation to effectively evaluate expert scientific testimony.…”
Section: Discussionsupporting
confidence: 88%
“…Given the high stakes (e.g., prison versus mental health hospital) associated with insanity verdicts, several studies have outlined variables that support negative opinions toward the insanity defense. These variables have included conservative political affiliations (Tygart, 1992), favorable opinions toward capital punishment (Butler & Wasserman, 2006;Poulson, Wuensch, Brown, & Braithwaite, 1997), and greater misperception of insanity defense use and success (Bloechl et al, 2007).…”
mentioning
confidence: 99%